The lock-up privatisation blues - T. Smith (Law Text Culture, 1995)
when I was born daddy bought me some shares in a catering company then each christmas he's added in turn a security firm a laund - er - y some units to rent a fleet of buses a merchant bank an escort agency an engineering shop a basketball team a supermarket a hospital and a whole party of cuddly politicians